STUDI PERSEPSI IKATAN JURNALIS TELEVISI INDONESIA: PENGARUH PROMOSI, KREATIVITAS KONTEN, DAN BRAND IMAGE TERHADAP KEUNGGULAN KOMPETITIF CNN INDONESIA TV DENGAN IDENTITAS MEREK SEBAGAI VARIABEL MEDIASI - Hindra, Firdaus; Istianingsih, Istianingsih; Harry Mukti, Aloysius (Berajah Journal, 2025)
This study analyzes the effect of promotion, content creativity, and brand image on brand identity and competitive advantage, with brand identity as a mediating variable. The object of research is CNN Indonesia TV, involving 87 television Journalist as respondents. A quantitative approach was used with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method to analyze the relationship between variables. The results show that promotion, content creativity, and brand image have a positive effect on brand identity. However, promotion and content creativity do not have a significant effect on competitive advantage, while brand image has a negative effect on competitive advantage. On the other hand, brand identity is proven to have a positive effect on competitive advantage. Brand identity also serves as a significant intervening factor, mediating the influence between promotion and competitive advantage, content creativity and competitive advantage, and brand image and competitive advantage. These findings highlight the importance of brand identity in enhancing competitive advantage in the media industry.